Perancangan Enterprise Architecture untuk UMKM Pengolahan Produk Perikanan Menggunakan TOGAF ADM - Ningtyas, Mastuty Ayu; Ananda, Dahliar; Amri, Arni Muarifah; Atha Ningrum, Maharani Febhi (Jurnal Algoritma, 2025)
The use of information technology in the micro, small, and medium enterprises (MSMEs) sector for processing fishery products at PT. Anugrah Laut Indonesia plays an important role in improving operational efficiency and industrial competitiveness. However, most of the company's core business processes are not yet running optimally due to the absence of an integrated system architecture blueprint as a guide for information system development. This condition has resulted in key operational activities, such as sales, raw material procurement, production, and distribution, not being adequately documented and integrated. Therefore, it is necessary to design an Enterprise Resource Planning (ERP) architecture that integrates information technology to align business needs and improve operational efficiency. This study uses a qualitative approach, with architecture design based on The Open Group Architecture Framework, Architecture Development Method (TOGAF ADM), and focuses on three main phases: Architecture Vision, Business Architecture, and Information System Architecture. The results of this study are in the form of an IT blueprint design that describes the integration of key business processes, data requirements, and information system plans to support improved operational efficiency and decision making.